1997
DOI: 10.1002/(sici)1097-0290(19970205)53:3<259::aid-bit3>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a styrene‐degrading biofilter containing the yeast Exophiala jeanselmei

Abstract: A general mathematical model developed for a description of pollutant degradation in a biofilm was used to evaluate the performance of a biofilter for the purification of styrene-containing gas. The biofilter contained perlite as an inert support on which a biofilm was present composed of a mixed microbial population containing the fungus Exophiala jeanselmei as a major styrene-degrading microorganism. Although styrene is a moderately hydrophobic compound, the biofilter was reaction limited at a styrene gas ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 21 publications
8
70
0
7
Order By: Relevance
“…The fact that many fungal species are able to degrade the VOCs present in the waste gas stream, however, raises the distinct possibility that they contributed to VOC removal. 21,[25][26][27][28][29][30] No attempt was made to enumerate microbial populations in Biofilter 2, so a direct comparison between the two systems is not possible. As described in the following section, however, differences in the quantity of biomass between the two systems were readily apparent from microscopy analysis.…”
Section: Plate Count Datamentioning
confidence: 99%
“…The fact that many fungal species are able to degrade the VOCs present in the waste gas stream, however, raises the distinct possibility that they contributed to VOC removal. 21,[25][26][27][28][29][30] No attempt was made to enumerate microbial populations in Biofilter 2, so a direct comparison between the two systems is not possible. As described in the following section, however, differences in the quantity of biomass between the two systems were readily apparent from microscopy analysis.…”
Section: Plate Count Datamentioning
confidence: 99%
“…Lower pollutant removal performance was expected since styrene is known to be much more difficult to biodegrade than CH 2 Cl 2 is. 18,21 On average, styrene inlet concentrations ranged from 0.5 to 1 g/m 3 . At the startup, the reactor was inoculated with activated sludge, and early performance monitoring of the reactor showed that styrene elimination capacity was 15 g/m 3 /hr with 70% removal efficiency ( Figure 4).…”
Section: Reactor Performancementioning
confidence: 99%
“…Interestingly, Hartmans, van der Werf & de Bont (1990) isolated two fungi able to grow on styrene as a sole carbon and energy source. One of those strains, the yeast-like fungus Exophiala jeanselmei, was used successfully for treating of styrene-polluted air in a biofilter , Cox et al 1997. More recently, the deuteromycete Cladosporium sphaerospermum was isolated from a biofilter that had been used to remove toluene from contaminated air.…”
Section: Introductionmentioning
confidence: 99%